Simulation analysis of fatigue strength in steel highway bridges - Wysokowski, Adam (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this paper, the determination in a theoretical way ? by the simulation analysis - of the stress spectra and strength, as well the service life parameters for the structural elements of road bridges is presented. The analytically obtained results have been verified by the results from field tests of selected elements of steel road bridges under the service load. For the simulation calculations, a linear load model of road bridges (presented in the paper) has been applied, derived from author's measurements on structures and concerning traffic on the Polish urban and country roads and bridges. The presented studies and theoretical analyses have proved that the fatigue hazard exists also in road bridges and they have indicated what types of bridges, which bridge elements in what static schemes, which spans and under what service loads, are endangered by the fatigue hazard.
Keywords: most drogowy; konstrukcje stalowe; wytrzymałość; zmęczenie; analiza symulacyjna; highway bridges; steel structures; fatique; simulation analysis